The xVA challenge : counterparty credit risk, funding, collateral, and capital - Gregory, Jon, 1971- (Chichester, West Sussex, UK : John Wiley & Sons, 2015)
'A detailed, expert-driven guide to today's major financial point of interest The xVA Challenge: Counterparty Credit Risk, Funding, Collateral, and Capital is a practical guide from one of the leading and most influential credit practitioners, Jon Gregory. Focusing on practical methods, this informative guide includes discussion around the latest regulatory requirements, market practice, and academic thinking. Beginning with a look at the emergence of counterparty risk during the recent global financial crisis, the discussion delves into the quantification of firm-wide credit exposure and risk mitigation methods, such as netting and collateral. It also discusses thoroughly the xVA terms, notably CVA, DVA, FVA, ColVA, and KVA and their interactions and overlaps. The discussion of other aspects such as wrong-way risks, hedging, stress testing, and xVA management within a financial institution are covered. The extensive coverage and detailed treatment of what has become an urgent topic makes this book an invaluable reference for any practitioner, policy maker, or student. Counterparty credit risk and related aspects such as funding, collateral, and capital have become key issues in recent years, now generally characterized by the term'xVA'. This book provides practical, in-depth guidance toward all aspects of xVA management. Market practice around counterparty credit risk and credit and debit value adjustment (CVA and DVA) The latest regulatory developments including Basel III capital requirements, central clearing, and mandatory collateral requirements The impact of accounting requirements such as IFRS 13 Recent thinking on the applications of funding, collateral, and capital adjustments (FVA, ColVA and KVA) The sudden realization of extensive counterparty risks has severely compromised the health of global financial markets. It's now a major point of action for all financial institutions, which have realized the growing importance of consistent treatment of collateral, funding, and capital alongside counterparty risk. The xVA Challenge: Counterparty Credit Risk, Funding, Collateral, and Capital provides expert perspective and real-world guidance for today's institutions'--
'This book explains the emergence of counterparty risk during the recent credit crisis. The quantification of firm-wide credit exposure for trading desks and businesses is discussed alongside risk mitigation methods such as netting and collateral management (margining) and central counterparties. Banks and other financial institutions have been recently developing their capabilities for pricing counterparty risk and these elements are considered in detail via a characterisation of credit value adjustment (CVA). The implications of an institution valuing their own default via debt value adjustment (DVA) and funding costs (FVA) are also considered at length. Portfolio management and hedging of CVA are described in full. Wrong--way counterparty risks are addressed in detail in relation to interest rate, foreign exchange, commodity and credit derivative products. Regulatory capital for counterparty risk, including the recent Basel III requirements for CVA VAR is discussed. The management of counterparty risk within an institution by a'CVA desk' is also discussed in detail. Finally, the design and benefits of central clearing, a recent development to attempt to control the rapid growth of counterparty risk, is considered. Hedging aspects, together with the associated instruments such as credit defaults swaps (CDSs) and contingent CDS (CCDS) are described in full. This book is unique in being practically focused but also covering the more technical aspects. It is an invaluable complete reference guide for any market practitioner, policy maker, academic or student with any responsibility or interest within the area of counterparty credit risk and CVA'--
Revised edition of the author's Counterparty credit risk and credit value adjustment, 2012.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Derivative securities -- Mathematical models; Risk management; Electronic books